The administration of Cecil John Rhodes as prime minister of the Cape Colony, 1890-1896 - Jenkins, Stanley John (Department of Historical Studies, 2015)
In his monograph, Sir Thomas Fuller divides Rhodes's public policy under three heads - the expansion of the Cape Colony; the federation, or, as it was frequently called, the union of South African States; and the Government of the Cape Colony itself when he became its Premier. Any such divisions are of course merely arbitrary, and merely made for the sake of convenience, for it is obvious that these aspects of his policy were closely inter-related, and, in fact, inter-dependent. For this reason, it is all the more to be regretted that in the Imperialistic fervour which hallows the memory of Rhodes abodes the Empire-builder, or at the other extreme, in the severe condemnation of the Rhodes of the Jameson Raid, the significance of his work as Prime Minister of the Cape Colony is under-estimated or over- looked altogether. The Colony provided the base for his operations in the wider field of South African politics. Without its support, there could have been no Northern development, and in his scheme of South African unity, he believed it the Colony's destiny to play the leading role. Thus during his Premiership, the Franchise changes were introduced as a step towards a common South African Native policy; the Glen Grey Bill was a "Native Bill for Africa"; in regard to railways and customs, the ultimate aim was amalgamation and free trade in South African products as a prelude to political unity. Above all, it was a period of close co-operation between the two sections of the European population in the Colony itself, and it is this aspect of Rhodes's administration with which this thesis is primarily concerned. It has also been necessary to deal at some length with his earlier activities to show how this co-operation became possible, and to trace its effect upon the general trend of his policy after 1890.